External financing and earnings management: Evidence in Vietnam - Phuong Bui; Hai Ngo; Khuong Nguyen Vinh; Nguyen Thanh Liem (Cogent Economics & Finance, 2022)
This paper investigates the effect of external financing on earnings management in Vietnam, a bank-dominated economy. Using a sample of 494 listed non-financial firms from 2009 to 2018, we find that external financing is positively related to earnings management, implying that firms have incentives to manage earnings raising external fund. Additionally, earnings are manipulated when firms conduct capital raising by issuing either equity or debt. However, compared to debt financing, earnings are managed more aggressively when firms are involved in equity financing activities. Finally, we extend the literature by showing that equity is especially destructive at high levels. These findings lend credence to the argument that firms issuing equity have stronger incentives to manage earnings than debt issuers and call for thorough monitoring and scrutiny of stakeholders towards this type of issuance.
Keywords: D82; G30; G32; M41; 330; Asymmetric information; debt financing; earnings management; equity financing; external financing